(3QSGdI aj GdYbds - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI ai GdYbhd RYehG Cf GdHGQi JYGdi dGMO dg hdG QSe dCfg hGdMO jdJFe HGdLfS hGdYhGQV GdYGeI s
(3BNQgG (B:s
(3heG PcQfGg TQM GdGSe hGdMeO dQHfG GdeMehO hdg GdecGQe hdg GdecGQe hdg GdYdi hGdLhO hGdUdGg hGdSdGe Ydi QShdg hMHjHg GdPi CSeg ai GdGQV eMeO hai GdSeGA eMehO hYdi Gdg GdcQGe hGUMGHg GdYXGe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs